Short-term isolation effects on the brain, cognitive performance, and sleep—The role of exercise - Klein, Timo; Braunsmann, Leonard; Koschate, Jessica; Hoffmann, Uwe; Foitschik, Tina; Krieger, Stephanie; Crucian, Brian; Schneider, Stefan; Abeln, Vera (Frontiers in Physiology, 2023)
Isolation is stressful and negatively affects sleep and mood and might also affect the structure and function of the brain. Physical exercise improves brain function. We investigated the influence of physical exercise during isolation on sleep, affect, and neurobehavioral function. N = 16 were isolated for 30 days with daily exercise routines (ISO100) and n = 16 isolated for 45 days with every second day exercise (ISO50). N = 27 were non-isolated controls who either exercised on a daily basis (CTRLEx) or refused exercise (CTRLNonEx) for 30 days. At the beginning and the end of each intervention, intravenous morning cortisol, melatonin, brain-derived neurotrophic factor and IGF-1, positive and negative affect scales, electroencephalography, cognitive function, and sleep patterns (actigraphy) were assessed. High levels of cortisol were observed for the isolated groups (p < .05) without negative effects on the brain, cognitive function, sleep, and mood after 4 to 6 weeks of isolation, where physical exercise was performed regularly. An increase in cortisol and impairments of sleep quality, mood, cognitive function, and neurotrophic factors (p < .05) were observed after 4 weeks of absence of physical exercise in the CTRLNonEx group. These findings raise the assumption that regular physical exercise routines are a key component during isolation to maintain brain health and function.